DETERMINAN MINAT BERPROFESI DALAM BIDANG PERPAJAKAN - Dewi, Indira Shinta; Christina, Christina; Tresnawaty, Nia (Unversitas Prof. Dr. Moestopo (Beragama), 2024)
This research aims to identify and empirically test the factors that influence the interest of students who participate as tax opponents in government programs at the Tax Service Office to pursue a career in the field of taxation, by considering the variables of attitude, subjective norms and knowledge. This research uses a quantitative approach, with data collected through questionnaires distributed to 220 respondents. The purposive sampling method and Likert scale were used to analyze the data. Tax volunteer participants from 2021 to 2024 who are students from universities collaborating with the South Jakarta II DJP Regional Office are the population in this research. Research using SPSS software partially shows that attitudes and knowledge of taxation influence tax volunteers' interest in working in the taxation field, while subjective norms do not influence tax volunteers' interest in taxation.